Shear Bond Strength of Composite-Resin to Porcelain: Effect of Thermocycling - M. Khoroushi; Sh. Motamedi (Tehran University of Medical Sciences, 2007)
Objective: Different ceramic repair systems have been reported for fractured ceramics. However, limited information is available concerning the bond strength of these systems especially after thermocycling. The aim of this in-vitro study was to determine the effect of thermocycling on the shear bond strength of composite-resin to feldspathic porcelain with and without silane pretreatment. Materials and Methods: In this experimental study, forty porcelain blocks were prepared and randomly divided into four groups (n=10). All porcelain surfaces were etched with 9.6% hydrofluoric acid, rinsed and air dried. In groups 1 and 3, silane pretreatment was applied using Adper Scotchbond Multipurpose Plus (ASMP). Small-particle composite-resin was subsequently added on the ceramic surfaces, and light-cured. Specimens of groups 3 and 4 then subjected to 1000 thermal cycles. Shear bond strength was determined on a universal testing machine at a crosshead speed of 1mm/min. Two-way ANOVA test (a=0.05) was used to analyze the bond strength. Results: There were statistically significant differences between study groups (P<0.05). Thermocycling caused a decrease in the shear bond strength for both silanized and non-silanized groups. Conclusion: According to the results of this study, shear bond strength after thermocy-cling reduced considerably in ASMP system. In addition, silane treatment of porcelain was critical for achieving durable bond strength between composite-resin and porcelain.